2011
DOI: 10.1093/nar/gkr568
|View full text |Cite
|
Sign up to set email alerts
|

Conformational change of single-stranded RNAs induced by liposome binding

Abstract: The interaction between single-stranded RNAs and liposomes was studied using UV, Fourier Transform Infrared spectroscopy (FTIR) and Circular Dichroism spectroscopy (CD). The effect of the surface characteristics of liposomes, which were composed of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and modified with cholesterol (Ch) or 1,2-dioleoyl-3-trimethylammonium propane (DOTAP), on the liposome–RNA interaction was investigated. The fluorescence of 6-(p-toluidino)naphthalene-2-sulfonate (TNS) embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(97 citation statements)
references
References 42 publications
5
91
1
Order By: Relevance
“…The ΔGP 340 value of DOTAP was highest among the liposomes used in this study, although the change in the GP 340 value of DOTAP was not as significant as compared to the phase transition from the liquiddisordered phase to the solid-ordered phase. 29 BNO could be embedded in the hydrophobic−hydrophilic interface region where water molecules bind, and could replace the water molecules, resulting in the dehydration of the membrane The Journal of Physical Chemistry B Article surface (i.e., an increase in the GP 340 value). Here, a few percent of water was excluded from the liposome membrane (the relative dielectric constant ε′ varied to 25.0 from 26.3; see below).…”
Section: The Journal Of Physical Chemistry Bmentioning
confidence: 99%
“…The ΔGP 340 value of DOTAP was highest among the liposomes used in this study, although the change in the GP 340 value of DOTAP was not as significant as compared to the phase transition from the liquiddisordered phase to the solid-ordered phase. 29 BNO could be embedded in the hydrophobic−hydrophilic interface region where water molecules bind, and could replace the water molecules, resulting in the dehydration of the membrane The Journal of Physical Chemistry B Article surface (i.e., an increase in the GP 340 value). Here, a few percent of water was excluded from the liposome membrane (the relative dielectric constant ε′ varied to 25.0 from 26.3; see below).…”
Section: The Journal Of Physical Chemistry Bmentioning
confidence: 99%
“…The interaction mechanism of liposomes with biomacromolecules has been recently investigated [42,48], focusing on the recognition, folding, and functionalization by selecting single-stranded RNA molecules as targets ( Figure 6). Liposome surfaces were modified with Ch, DOTAP, and DC-Ch, and the physicochemical properties of the liposomes were analyzed by using the fluorescent probes, DPH and …”
Section: "Liposome Membrane Design" For Recognition Of Biomacromoleculesmentioning
confidence: 99%
“…It was shown that the liposomes affected the conformation of single-stranded RNAs [42,[45][46][47][48], which is a key parameter affecting their functions [53][54][55]. The dependence of the liposome-RNA interaction on the phase state of the CLs is also discussed.…”
Section: Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…Emergent properties arising from the membrane of the liposome (vesicle) have been introduced, where the vesicle (liposome) membrane can selectively interact with various types of molecules under particular conditions. 12 The important functions of vesicles include (1) interaction with proteins (enzymes) and nucleotides, [13][14][15][16][17] (2) storage of encapsulated molecules, 1,18 and (3) fusion with membranes. 19 Vesicle membranes are dynamic, for example, vesicles composed of 1,2-dimylistoyl-sn-glycero-3-phosphocholine (DMPC) and 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) possess phase transition temperatures (T m ) at 23.6 and 41.…”
Section: Introductionmentioning
confidence: 99%